Moluscos terrestres do Brasil (Gastrópodes operculados ou não, exclusive Veronicellidae, Milacidae e Limacidae) - Campos Salgado, Norma (2003)
Studies on terrestrial prosobranchs (streptoneureans) and shelled pulmonates (euthyneureans) show the significant diversity of the Brazilian malacofauna. These mollusks are still poorly known, despite the increasing interest in the group that started in the XVIII century when land mollusks began to be collected and deposited in scientific collections. The species are arranged in alphabetical order; the taxonomic combination is updated when possible with the original and other bibliographic references. This checklist includes original study of specimens deposited in Brazilian, American and European collections, as well as names and additional data of important early naturalists and current researchers of the group. Species are here associated to their original references; geographical distribution and other taxonomic references were added to each. A total of 590 species were found (27 families and 95 genera). The systematic arrangement of suprageneric and generic taxa was based on Taylor & Sohl (1962), Thiele (1929-1931), Wenz (1938-1944) and Zilch (1959-1960). Breure (1973-1985) was especially useful regarding Bulimuloidea because the characteristics of some subgenera justified a raise to generic level. The consistent characteristics found in some controversial subspecies justify a species rank for them.